Amor Mundi e educação em Hannah Arendt - RODRIGUES, Cláudia Raissa Silva (2023)
This work presents a reflection on the world, education and authority based on the thinking of the author Hannah Arendt. It seeks to establish a dialogue with the definitions of the public and private spheres, as well as with the concept of the common world, analyzing from the polis to modernity the relationship between human beings and the world. For Arendt, the world is the space shared by all, where we can be seen and heard and thus preserve that place. From this perspective of preservation, we approach authority and education, exploring the crisis experienced by these two spheres and the impact of this on the crisis of the modern world, which is based neither on authority nor on tradition. Both tradition and authority are tolerated in order to understand the education crisis and ensure the permanence of the world. The analysis also reflects on the case of Little Rock as a backdrop to discuss the author's education and thinking in relation to natality and plurality. We seek to understand the meaning of newcomers to the world and the importance of authority in education, both in the school and family environment. It is important to emphasize that the author is not an education specialist, but a philosopher who reflects on education and the world through a phenomenological approach. We seek to understand, therefore, the legacy to be left by newcomers and the reconciliation of human beings with the world, considering the impact of authority on education and the importance of reflecting on the meaning of school and family life.